Detoxification effects of ascorbic acid on the oxidative stress, neurotoxicity, and metallothionein (MT) gene expression in juvenile rockfish, Sebastes schlegelii by the dietary chromium exposure. Issue 132 (January 2023) - Kim, Jun-Hwan; Kang, Ju-Chan
Abstract: Juvenile rockfish Sebastes schlegelii (mean length 10.8 ± 1.4 cm, and mean weight 31.7 ± 3.6 g) were exposed for 4 weeks with the different levels of dietary chromium (Cr 6+ ) at 0, 120 and 240 mg/L and ascorbic acids (AsA) at 100, 200 and 400 mg/L. Superoxide dismutase (SOD) activity, glutathione S-transferase (GST) activity, and glutathione (GSH) level of liver and gill were evaluated as antioxidant response indicators for the 4 weeks exposure. The SOD and GST activity of liver and gill were substantially increased by the high concentrations of dietary Cr exposure, whereas a significant decrease was observed in the GSH levels of liver and gill. Metallothionein (MT) gene in liver was significant stimulated in the response to the dietary Cr exposure. In neurotoxicity, AChE activity was considerably inhibited in brain and muscle tissues by dietary Cr exposure. The high levels of AsA supplementation were highly effective to attenuate the alterations in the antioxidant responses, MT gene expression, and AChE activity by the dietary Cr exposure. Graphical abstract: Image 1 Highlights: The antioxidant responses in S. schlegelii were affected by the dietary Cr exposure. The MT gene expression was significantly stimulated by the Cr exposure. The AChE activity was inhibited by the Cr exposure as neurotoxicity. High level of AsA were effective to attenuate the Cr-induced toxicity.